Freshwater Scarcity and Sustainable Water Management in the Hindu Kush-Himalayan (HKH) Region - Gurung, Pabitra; Sherpa, Tashi Yang Chung (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Water is essential for every life on the earth and for many forms of socioeconomic development activity. Freshwater scarcity is a major issue in the developing world in terms of human consumption and irrigation. Water is not evenly distributed therefore some regions (particularly in South Asia and Africa) will experience intensified water scarcity in coming years. The stressors on water are population growth and climate change. These stressors are exacerbated by poor management and policy on the part of ruling governments. Climate change is of keen interest as it will impact water availability in unpredictable ways. In this context, it is essential to develop efficient adaptive tactics (e.g., water storage) to anticipate these changes. The paper, then, will look into the global scenario of water demand, as well as examine regional conflicts that may become worse under the stress of water scarcity. DOI: http://dx.doi.org/10.3126/hn.v15i0.11291 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 15, 2014, July Page: 42-47